Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen di Apotek Enggal Sehat Megang Sakti Kabupaten Musi Rawas - Fitria Fitria; Muhamad Effendi; Rudi Azhar; Nasruddin Nasruddin; Oktalina Windari (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the Marketing Mix on Consumer Purchasing Decisions at the Enggal Sehat Megang Sakti Pharmacy, Musi Rawas Regency. This research method is data collection using a questionnaire. The results of the Product Marketing Mix research have a significant effect on Consumer Purchasing Decisions. This is proven by the value of tcount = 4.004 > ttable value = 1.660 with a significant value of 0.000 < 0.05. The results of the second hypothesis test: Price Marketing Mix has a significant effect on Consumer Purchasing Decisions. This is proven by the tcount value = 3.628 > ttable value = 1.660 with a significant value of 0.000 < 0.05. The results of the third hypothesis test: Place Marketing Mix has a significant effect on Consumer Purchasing Decisions. This is proven by the value of tcount = 4.014 > ttable value = 1.660 with a significant value of 0.000 < 0.05. The results of the fourth hypothesis test: Promotional Marketing Mix have a significant effect on Consumer Purchasing Decisions. This is proven by the value of tcount = 3.627 > ttable value = 1.660 with a significant value of 0.000 < 0.05. The marketing mix has a significant effect on consumer purchasing decisions at the Enggal Sehat Pharmacy, Megang Sakti, Musi Rawas Regency. This is proven by the value of Fcount = 5.213 > ttable value = 2.456 with a significant value of 0.001 < 0.05. Conclusion, Marketing marketing influences consumer purchasing decisions at the Enggal Sehat Pharmacy. Keywords: Marketing Mix, Purchasing Decisions, Consumers